1997
DOI: 10.1074/jbc.272.42.26659
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That the β-Isoform of the Human Glucocorticoid Receptor Does Not Act as a Physiologically Significant Repressor

Abstract: Alternative splicing of the human glucocorticoid receptor (hGR) primary transcript generates two receptor isoforms, hGR␣ and hGR␤, with different carboxyl termini diverging at amino acid 727. By reverse transcriptase-polymerase chain reactions it was previously demonstrated that the hGR␤ message had a widespread tissue distribution. To demonstrate the presence of hGR␤ as protein we produced specific rabbit antisera to hGR␤, as well as a hGR␤-specific mouse monoclonal IgM antibody, by peptide immunizations. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 20 publications
2
97
2
Order By: Relevance
“…Glucocorticoid receptor ␣ binds corticosteroids, whereas glucocorticoid receptor ␤ is an alternatively spliced form that binds to DNA but is not activated by corticosteroids (see Glossary). Glucocorticoid receptor ␤ has been implicated in steroid resistance in asthma (18), although whether glucocorticoid receptor ␤ has any functional significance has been questioned (19). Glucocorticoid receptors may also be modified by phosphorylation and other modifications, which may alter the response to corticosteroids.…”
Section: Glucocorticoid Receptorsmentioning
confidence: 99%
“…Glucocorticoid receptor ␣ binds corticosteroids, whereas glucocorticoid receptor ␤ is an alternatively spliced form that binds to DNA but is not activated by corticosteroids (see Glossary). Glucocorticoid receptor ␤ has been implicated in steroid resistance in asthma (18), although whether glucocorticoid receptor ␤ has any functional significance has been questioned (19). Glucocorticoid receptors may also be modified by phosphorylation and other modifications, which may alter the response to corticosteroids.…”
Section: Glucocorticoid Receptorsmentioning
confidence: 99%
“…GRb exhibits a very low level of expression compared to GRa [22]. The GRb isoform has been implicated in steroid resistance in asthma [23], although whether GRb can have any functional significance has been questioned in view of the very low levels of expression compared to those of GRa [24].…”
Section: Glucocorticoid Receptorsmentioning
confidence: 99%
“…However, this was not always confirmed. 31 Most clinical evidence that GRb is capable of decreasing GC sensitivity of target cells has been obtained in respiratory medicine. Various authors showed that GRb expression in airway cells and peripheral blood mononuclear cells obtained from patients with GC-resistant asthma was higher than in patients with GC-sensitive asthma or normal s ubjects.…”
Section: Introductionmentioning
confidence: 99%